2012
DOI: 10.1016/j.ejphar.2012.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of myocardial dysfunction and autonomic imbalance contributes to the estrogen-dependent chronic hypotensive effect of ethanol in female rats

Abstract: Our previous studies showed that the hypotensive effect of chronic ethanol in female rats is reduced by ovariectomy (OVX) rats and was restored after estrogen replacement (OVXE2). Further, in randomly cycling rats, chronic ethanol increased cardiac parasympathetic dominance and subsequently reduced myocardial contractility and blood pressure (BP). In this study, we tested the hypothesis that alterations in myocardial contractility and sympathovagal control account for the E2 exacerbation of the hemodynamic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
5
13
0
Order By: Relevance
“…It should be remembered, however, that the 90-min observation period was employed here because the same time course was adopted in our previous studies that evaluated the BP and LV effects of ethanol in female rats (El-Mas and Abdel-Rahman, 1999b, 1999c, 2014). Moreover, similar to the acute setting, our previous reports showed that 3-month ethanol treatment caused hypotension, myocardial depression, and autonomic dysfunction in female rats, and these effects that were drastically reduced in ovariectomized rats and restored after simultaneous administration of E 2 (El-Mas and Abdel-Rahman, 2001, 2012b). …”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It should be remembered, however, that the 90-min observation period was employed here because the same time course was adopted in our previous studies that evaluated the BP and LV effects of ethanol in female rats (El-Mas and Abdel-Rahman, 1999b, 1999c, 2014). Moreover, similar to the acute setting, our previous reports showed that 3-month ethanol treatment caused hypotension, myocardial depression, and autonomic dysfunction in female rats, and these effects that were drastically reduced in ovariectomized rats and restored after simultaneous administration of E 2 (El-Mas and Abdel-Rahman, 2001, 2012b). …”
Section: Discussionsupporting
confidence: 52%
“…Sex-specific data analysis reveals that ethanol reduces BP in young, but not in older women (Klatsky, 1990), and causes cutaneous flushing in women receiving hormone replacement therapy (Nitzan and Dan, 2009). The role of sex hormones, particularly E 2 , is supported by the observations that the ethanol-evoked hypotension virtually disappears in ovariectomized (OVX) rats and is fully restored after chronic (El-Mas and Abdel-Rahman, 2012b) or acute E 2 administration (El-Mas and Abdel-Rahman, 2014). Evidence suggests that the male gender is protected against the direct cardiodepressant/hypotensive effect of ethanol by at least two mechanisms.…”
Section: Introductionmentioning
confidence: 97%
“…The power spectral analysis of hemodynamic variability, which revealed ethanol-evoked increase in the high (HFα), but not the low (LFα) frequency component of RRI, is consistent with a shift in the sympathovagal balance towards vagal dominance (Laitinen et al, 1999). These findings suggest that enhanced vagal dominance is implicated in the chronic cardiodepressant effect of ethanol in female rats (El-Mas et al, 2009, El-Mas and Abdel-Rahman, 2012b), and occurs within minutes following acute ethanol administration (Fig. 2).…”
Section: Discussionmentioning
confidence: 78%
“…Notably, recent advances in cardiovascular research have facilitated measurements of LVDP and d P /d t max as direct indices of cardiac contractility (Zhao et al, 2012, Lieber et al, 2008, Wang et al, 2004) in conscious animals along with assessment of sympathovagal control of the heart. Data based on the latter implicated cardiac vagal dominance in the E 2 -dependent chronic hypotensive effect of ethanol in female rats (El-Mas and Abdel-Rahman, 2012b, El-Mas and Abdel-Rahman, 2009). However, it is not known if acute ethanol similarly influences the sympathovagal control of heart rate in proestrus female rats, and the mechanisms of the myocardial depressant effect of alcohol are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The present studies were conducted in telemetered female rats at the conclusion of chronic-ethanol (5% w/v) or isocaloric liquid-diet feeding, described in our recent study (El-Mas et al, 2011), to investigate the effect of selective inhibition of constitutive and inducible NOS on the enalapril-evoked changes in BP, +dP/dt max , and spectral indices of hemodynamic variability. Spectral indices of hemodynamic variability are categorized into low-frequency interbeat intervals (IBI-LF; 0.25–0.75 Hz; reflect the sympathetic drive) and high-frequency interbeat intervals (IBI-HF; 0.75–3 Hz; reflect the cardiac vagal control), along with the ratio of LF to HF interbeat intervals (IBI LF/HF ), which is a measure of the sympathovagal balance of the heart (El-Mas and Abdel-Rahman, 2012; Thomas, 2011). The ethanol (5% w/v, 8 weeks) or isocaloric liquid diet was provided using a pair-feeding paradigm to ensure similar fluid and nutrient intakes as in our previous studies (El-Mas and Abdel-Rahman 2004; El-Mas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%